Islam transendental : menelusuri jejak-jejak pemikiran Islam Kuntowijoyo - Fahmi, M. (Muttakhidul), 1980- (Yogyakarta : Pilar Religia, 2005)
Critics of the thougts of Kuntowijoyo, a professor in culture regarding methods of Islamic studies in Indonesia.
Revision of the author's thesis (S1)--Universitas Islam Negeri Sunan Kalijaga, under title: Strukturalisme transendental, upaya menerapkan ajaran Islam dalam transformasi sosial umat Islam di Indonesia
Includes bibliographical references (p. 293-304) and index
Keywords: Islam -- Social aspects -- Indonesia